2010
DOI: 10.1186/1472-6874-10-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, incidence and risk factors of herpes simplex virus type 2 infection among pregnant Zimbabwean women followed up nine months after childbirth

Abstract: BackgroundHerpes simplex virus type 2 (HSV-2) is the leading cause of genital ulcer disease worldwide. The virus can be transmitted to neonates and there are scarce data regarding incidence of HSV-2 among women in pregnancy and after childbirth. The aim of this study is to measure the incidence and risk factors for HSV-2 infection in women followed for 9 months after childbirth.MethodsPregnant women were consecutively enrolled late in pregnancy and followed at six weeks, four and nine months after childbirth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
5
30
3
Order By: Relevance
“…Having multiple sexual partners or sex with a person who has multiple partners and young age of sexual debut were significantly associated with HSV-2 acquisition [1,5]. In addition, having any sexually transmitted diseases was a risk factor for HSV-2 seroconversion [8,12].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Having multiple sexual partners or sex with a person who has multiple partners and young age of sexual debut were significantly associated with HSV-2 acquisition [1,5]. In addition, having any sexually transmitted diseases was a risk factor for HSV-2 seroconversion [8,12].…”
Section: Introductionmentioning
confidence: 90%
“…HIV-positive women were five times more likely to have HSV-2 infection than were HIV-negative women in Mulago Hospital. However, in a study by Munjoma et al (2009), HIV serostatus was not found to be a risk factor for HSV-2 seroconversion in pregnancy [5]. There is a need to further explore a possible association between HIV and HSV-2 seroconversion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same study done by Bernstein et al (2012) in America, the prevalence of HSV-1 was 3.6% in patients with genital warts which was very low compared to the present study in which 54.5% of HSV-1 patients also had genital warts. In Tanzania, Msuya et al (2009) obtained a prevalence of 1.1% in HIV positive patients who had genital warts (Munjoma et al, 2010). Different methodological approaches may have different significance.…”
Section: Discussionmentioning
confidence: 99%